Factors Influencing Consumers' Behavioral Intention to Use Electronic Wallet: A Study of Touch ’n Go E-wallet - Ling, Wei Aw; Raam, Ashwinytaah; Binti Mohd Rizal, Auni Nadiah; Binti Niyas Ali, Azra Parvin; Khoiruwnia, Fadhilah; Satia Utama, A A Gde; Teoh, Kok Ban (AIBPM Publisher, 2023)
With the advancement of technology and implement of the fourth industrial revolution, digital wallet payment methods have appeared as the latest wave in the market. People can now enjoy cashless payments with a simple tap of a button. Due to the Covid-19 pandemic, digital wallet use among consumers significantly increased. The study was conducted to analyze the factors influencing users' behavioral intention in using the electronic wallet (e-wallet)- Touch ’n Go E-wallet. To explore, the collection of both primary and secondary data is done through several sources, and a digital questionnaire was produced to collect data and information from 150 respondents. We tested hypotheses using IBM SPSS Statistic software. The result indicated that perceived usefulness, perceived convenience, perceived trust, and perceived security of the Touch ’n Go E-wallet application significantly influence consumer behavioral intention using the e-wallet payment method.